2013
DOI: 10.7314/apjcp.2013.14.11.6791
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Investigation of Cytotoxic and Apoptotic Effects of Cynara L. Species in Colorectal Cancer Cells

Abstract: Apoptotic and cytotoxic activity of plant extracts obtaining from naturally growing Cynara syriaca in Turkey and cultivated C cardunculus against DLD1 colorectal cancer cells was determined. Extracts from wild and cultivated Cynara species were obtained from their vegetative parts and receptacles using hexane and applied with five different dose (0.1-1 mg/ml) as well as apigenin for MTT tests for three time periods (24, 48 and 72 hours). After cells were treated with IC 50 doses for each extract total DNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Here we investigated whether, a phytocomplex derived from Artichoke leaves extracts, affects malignancy of pleural mesothelioma. It has been previously reported that artichoke phenol extracts can promote apoptosis and impair invasiveness of different cancer cell lines [ 34 36 ]. We found that the artichoke extract exerts in vitro and in vivo a broad anti-tumoral effect by strongly affecting MPM growth, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we investigated whether, a phytocomplex derived from Artichoke leaves extracts, affects malignancy of pleural mesothelioma. It has been previously reported that artichoke phenol extracts can promote apoptosis and impair invasiveness of different cancer cell lines [ 34 36 ]. We found that the artichoke extract exerts in vitro and in vivo a broad anti-tumoral effect by strongly affecting MPM growth, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro and in vivo experiments have shown that Cynara scolymus exhibits choleretic, hepatoprotective, antibacterial, antinflammatory, antithrombotic and hypocolesterolemic properties [ 30 ] [ 31 ] [ 32 ] [ 33 ]. Artichoke extracts are reported to induce apoptosis and cytotoxic effects in cancer cells [ 34 ] [ 35 ] [ 36 ]. In the present report we aimed to demonstrate the anti-cancer activity of the artichoke leaf extract through direct experimental tests, through the normalizing effect of the extract on the cancer metabolic alterations and through the evidence of extract antitumoral activity due to its impact on signalling pathways of oncogenic significance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the pro-apoptotic (BAX) gene expression and a cell cycle inhibitor (p21) were induced, while the anti-apoptotic BCL-2 gene expression was reduced in the extract's presence. However, a BAX/BCL-2 ratio increment was detected, which implied that the Cynarae flos extract had the ability to induce the intrinsic apoptotic pathway (68). Additionally, the phytochemical composition, which includes polyphenolic compounds, inhibits angiogenesis related to cancer (69).…”
Section: Cytotoxic Activity Of the Selected Herbal Extractsmentioning
confidence: 99%
“…Artichoke polyphenolic extracts had cytotoxic and apoptotic effects on colorectal cancer cells. It has been found that the proapoptotic BAX gene expression and a cell cycle inhibitor p21 CIP/WAF1 were induced in the presence of artichoke polyphenols [ 117 ]. Polyphenolic extracts from the edible part of artichoke (AEs) exhibited cancer cytotoxic activity on a human hepatoma cell line [ 118 ] as well as on other cell lines derived from various human tissues.…”
Section: Advances and Novelty In Cancer Chemoprevention And Treatmmentioning
confidence: 99%